Współczesna prasa funeralna – gatunki i tematy - Hodak, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
This article presents a variety of press genres, as well as the issues which are tackled in funeral magazines. On the Polish niche press market, there are three periodicals published regularly: “Memento”, “Kultura Pogrzebu” and “Biuletyn Polskiej Izby Pogrzebowej”. Their target readers are people engaged in the funeral business. The typical reporting genres used in such papers are: information or reports from trade meetings, or their combinations. The main areas of interest are: the law, the firm, the trade organization, history and funeral customs. This publication also addresses the characteristics of the language and style used. These magazines serve several purposes such as informing, creating opinion forums, helping in solving difficult problems, creating a trade forum so as to integrate the funeral society.